Intervensi Sosial Pada Pemerlu Atensi Sosial Di UPTD Pelayanan Dan Rehabilitasi Sosial Mardi Guna Lampung - Aditya Fajar Yudhanto; Luthfi Salim; Faisal Adnan Reza (Jurnal Sosiologi Nusantara, 2025)
The increasing number of homeless and beggars in urban areas, including Bandar Lampung, reflects the limited scope of social intervention for Social Attention Needers (PAS), consisting of individuals who face various social barriers such as unstable housing, broken family ties, and lack of skills. This study aims to examine the patterns and strategies of social intervention implemented by the Social Rehabilitation UPTD Mardi Guna Lampung. A qualitative method with a phenomenological approach was employed to explore social reality from the subjects' perspectives, utilising interviews, observations, and documentation. The results of the study showed that the pattern of social intervention was carried out through the identification, assessment, coaching program, resocialization, evaluation, and termination stages. The strategies employed involve a personal approach by social workers and cross-agency collaboration to support the program's success. In general, the resocialization process exhibits positive tendencies, although some beneficiaries continue to face challenges, particularly due to limited family support and unstable socioeconomic conditions. The analysis, using Max Weber's theory of social action, reveals that the interventions reflect purposeful, rational actions, rather than merely administrative routines. These findings highlight the significance of the quality of social workers’ actions and environmental support in achieving the success of social interventions for PAS.